Judicial Disparities in Premeditated Murder Cases: Legal Certainty in the Interpretation of Articles 338 and 340 of the Indonesian Criminal Code - Tanto Satryatama; Andika Wijaya; Satriya Nugraha; Rizki Setyobowo Sangalang (CV. Era Digital Nusantara, 2026)
Judicial disparities in homicide cases involving indications of premeditation continue to challenge legal certainty in Indonesia's criminal justice system. Previous studies have primarily examined sentencing disparity or the interpretation of Article 340 of the Indonesian Criminal Code (KUHP) in individual cases, but have not systematically explained the relationship between legal certainty, judicial discretion, and judicial reasoning through comparative analysis of judicial decisions. This study addresses that gap by analysing inconsistencies in the interpretation of the element